Interstitial Lung Disease in Neonates: A Long Road Is Being Paved - N. Kh. Gabitova; I. N. Cherezova; Ahmed Arafat; Dinara Sadykova (MDPI AG, 2023)
Background: Interstitial lung disease (ILD) is one of the most difficult conditions in pulmonology due to difficulties in diagnosing, classifying, and treating this condition. They require invasive approaches to diagnose (e.g., lung biopsy), non-applicable methods (e.g., lung function tests in newborns), or potentially non-accessible methods (e.g., genetic testing in not-well-equipped facilities, and several weeks are required for results to be announced). They represent a heterogeneous group of diseases in which the alveolar epithelium, parenchyma, and capillaries of the lungs are damaged, which leads to changes in the pulmonary interstitium, proliferation of connective tissue, and thickening of the alveolar-capillary membranes and alveolar septa. These changes are accompanied by impaired oxygen diffusion, progressive respiratory failure, and radiographic signs of bilateral dissemination. Although adult and child classifications for ILD have evolved over the years, classification for ILD in neonates remains a challenge. Case presentation: Here we discuss ILD in neonates briefly, and report two rare cases of ILD (a male white neonate, two-day-old with fibrosing alveolitis, and another male white neonate, one-day old with desquamative interstitial pneumonitis), with these diagnoses initially thought to be presented only in adulthood. Lung biopsy and histopathological findings of the two neonates have shown mononuclear cells in the alveolar spaces, and thickening of the alveolar walls confirmed the diagnosis of fibrosing alveolitis in one neonate, and desquamation of the large mononuclear cells in the intra-alveolar space in the other neonate, with the diagnosis of desquamative interstitial pneumonitis being confirmed. Interstitial lung disease lacks a consensus guideline on classification and diagnosis in neonates, rendering it one of the greatest challenges to pediatricians and neonatologists with remarkable morbidity and mortality rates. Conclusions: Fibrosing alveolitis and desquamative interstitial pneumonitis (DIP) are not adult-only conditions, although rare in neonates, histopathological examination and clinical practice can confirm the diagnosis. Based on our clinical practice, prenatal and maternal conditions may serve as potential risk factors for developing IDL in neonates, and further studies are needed to prove this hypothesis.